Validation of Survey Data on Income and Employment: The ISMIE Experience - Annette Jäckle; Emanuela Sala; Stephen P. Jenkins; Peter Lynn (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
This report derives from the project ?Improving survey measurement of income and employment (ISMIE)? which investigates measurement error in survey data on income and employment, using a UK sub-sample of the European Household Community Panel (ECHP). In this paper we describe the process of collecting validation data and the outcomes of the process. Validation data were obtained from two sources: employers? records and government benefit data from the Department for Work and Pensions (DWP). The former provided information on occupation and employment status, gross and net pay, membership of company pension schemes and industry sector. The latter provided histories of benefit receipt and tax credits, for example, child, disability, housing and unemployment benefits, pensions and income support.In the survey interview, respondents were asked for written permission both to obtain their DWP records and to contact their employer. They were also asked to provide information that would facilitate the process of obtaining the validation data: National Insurance number (NINO) and employer contact details. Subsequently, DWP records were extracted using a nonhierarchical matching strategy, based on different combinations of identifying variables obtained in the survey (NINO, sex, date of birth, name and postcode), and a survey of employers was carried out (mail, with telephone follow-up). The representativeness of the validation samples obtained depends on the co-operation of both survey respondents and providers of validation data, as well as errors in the matching process. We report permission rates, proportions providing matching items, match rates for the DWP data and response rates to the employer survey. We identify correlates of these measures of success at each stage of the validation process in terms of substantive characteristics of the survey respondents. Variation by subgroups is identified and implications for the representativeness of the validation sample are discussed.
Keywords: 330